2020
DOI: 10.1111/jfpe.13367
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐steam combination process for microbial decontamination and heat transfer enhancement

Abstract: Steam is by far the most effective heating medium used in commercial thermal processing applications. However, for rapid short time direct heating of food products it poses some serious difficulties because of the presence of air along the surface and internal tissues of the food products interferes with the heat transfer mechanism and slows down the effective heating of the surface. Addition of an ultrasound environment to steam can assist in removing this surface barrier and promote better heat transfer. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Physical methods are more likely to win the hearts of consumers than chemical methods in the future. While ultrasound technology or chemical treatments have been successfully used independently in a variety of food processing applications, their combination has not been widely tried and the future promises to reduce the use of chemical reagents and improve the quality and safety of fruit and vegetables [ 127 ].…”
Section: Shortcomings and Perspectives Of Ultrasound Technologymentioning
confidence: 99%
“…Physical methods are more likely to win the hearts of consumers than chemical methods in the future. While ultrasound technology or chemical treatments have been successfully used independently in a variety of food processing applications, their combination has not been widely tried and the future promises to reduce the use of chemical reagents and improve the quality and safety of fruit and vegetables [ 127 ].…”
Section: Shortcomings and Perspectives Of Ultrasound Technologymentioning
confidence: 99%
“… Short-time heating with ultrasound lowers the microbial ( E. coli ) load. [116] Ultrasound and 80 ppm nisin-ultrasound Ultrasound on total aerobic bacteria, yeast, and mold; physical and nutritional quality of fresh carrot juice. Nisin-assisted ultrasound has the best result in hindering total aerobic bacterial.…”
Section: Application Of Power Ultrasound In the Washing Of Fruits And Vegetablesmentioning
confidence: 99%
“…Boiling water blanching (BWB) and high-temperature steam (HTS) are the most common methods of thermal processes, which often lead to quality loss and nutrient loss [ 11 , 12 ]. Steam is a versatile heating medium that can retain the original color of food and has little effect on the quality of food [ 13 , 14 ]. Ju [ 15 ] et al processed Inonotus Obliquus with steam and found that soluble phenolic content and antioxidant activity were enhanced.…”
Section: Introductionmentioning
confidence: 99%